2015
DOI: 10.2527/jas.2014-7906
|View full text |Cite
|
Sign up to set email alerts
|

Growth parameters, behavior, and meat and ham quality of heavy pigs subjected to photoperiods of different duration

Abstract: To attain a good level of animal welfare, pigs require a sufficient environmental illumination. Therefore, minimum levels for light duration and light intensity have been set up by the European legislation (Directive 2008/120). An experimental trial was designed to determine whether an increased duration of the photophase (up to 16 h of light per day) could modify the behavior, productive parameters, and meat and ham quality of Italian heavy pigs. Forty crossbred (Large White × Landrace) castrated males pigs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…A few studies investigated the behavioural traits of heavy pigs. The results from the present trials are in substantial agreement with previous finding from our research group (Scipioni et al 2009, Martelli et al 2015 confirming that heavy pigs tend to spend most of the daily hours (at least 60%) lying in resting position (either lateral or sternal recumbency). In both trials behaviour significantly differed between the two experimental groups.…”
Section: Discussionsupporting
confidence: 93%
“…A few studies investigated the behavioural traits of heavy pigs. The results from the present trials are in substantial agreement with previous finding from our research group (Scipioni et al 2009, Martelli et al 2015 confirming that heavy pigs tend to spend most of the daily hours (at least 60%) lying in resting position (either lateral or sternal recumbency). In both trials behaviour significantly differed between the two experimental groups.…”
Section: Discussionsupporting
confidence: 93%
“…However, this light condition impairs explorative behavior. The welfare of the animals might be improved by an appropriate light regimen, as found, for example, by Martelli et al [ 48 ].…”
Section: Procedures Management Practices and Housing Conditions mentioning
confidence: 99%
“…It has been reported that the raw hams from pigs of a longer photoperiod group (14L:10D) had a higher saturation degree of subcutaneous fat than pigs of a shorter photoperiod group (8L:16D) ( Sardi et al., 2012 ). Martelli et al. (2015) also reported that the hams from the longer photoperiod group had a lower weight loss during the dry-curing period than the shorter photoperiod counterpart.…”
Section: Introductionmentioning
confidence: 89%